Deforestation Simplifies Understory Bird Seed-Dispersal Networks in Human-Modified Landscapes - Menezes Pinto, Ícaro; Emer, Carine; Cazetta, Eliana; Morante-Filho, José Carlos (Frontiers in Ecology and Evolution, 2021)
Global biodiversity is threatened by land-use changes through human activities. This is mainly due to the conversion of continuous forests into forest patches surrounded by anthropogenic matrices. In general, sensitive species are lost while species adapted to disturbances succeed in altered environments. However, whether the interactions among the persisting species are also modified, and how it happens throughout the resulting landscape are still to be uncovered. Here we evaluated how landscape predictors (forest cover, total core area, edge density, inter-patch isolation) and local characteristics (fruit availability, vegetation complexity) affected the understory birds seed-dispersal networks in 19 forest sites along the hyperdiverse yet highly depauperate northeast distribution of the Brazilian Atlantic Forest. We assessed the effects of local and landscape-scale predictors on several network metrics (number of interactions, links per species, interaction evenness, and modularity). We found that the number of interactions was positively affected by the amount of forest cover, and it was significantly lower in the more deforested region. Counterintuitively, the number of fruits and vegetation complexity did not affect the structural parameters of these networks. We also observed a lack of significant network structure compared to null models, which we attribute to a pervasive impoverishment of the bird and plant communities in these highly modified landscapes. Our findings demonstrate the importance of forest cover not only to maintain species diversity but also their respective mutualistic relationships, which are the bases for ecosystem functionality, forest regeneration and the provision of ecological services.